# math question?

Favorite Answer

and is it

-2x-4x+4=0 ??

i’ll give it a go…

-2x-4x+4=0

-2x-4x=0-4

-6x= -4

now you have to get rid of the -6

-6x/-6= -4/-6

x= 0.6

Check:

-6 x 0.6= – 3.6

round it.

-6 x 0.6= -4

-2x^2-4x+4=0

Then you have to factor it. You can use the quadratic formula as somebody pointed out, or you can do it mentally. I’d do it like this:

1) factor out a -2

-2(x^2+2x-2)=0

2) cancel the -2 (divide by -2 on both sides)

x^2+2x-2

2) factor the expression

(x- )(x+ )=0

to fill in the blanks you know that -2 factors into 1 and 2 (one of them is negative, hence the one + sign and one -, but you don’t know which one)

The problem is, it doesn’t factor into intergers, so you have no choice but to use the quadratic formula. Right now, you have the equation in standard form:

Ax^2+Bx+C=0

A=1

B=2

C=-2

Then you plug those values into the formula:

(-B+sqrt(B^2-4AC))/2A

and

(-B-sqrt(B^2-4AC))/2A

you get two different values for x, and they are:

-1+sqrt(3)

and

-1-sqrt(3)

I hope it helped.

Anyways,

The roots are found when -2x^2 – 4x + 4 = 0, so

-2x^2 – 4x + 4 = 0

-2(x^2 + 2x – 2) = 0

x^2 + 2x – 2 = 0

Using the formula x = [-b +- sqrt(b^2 – 4ac)] / 2a,

x = 0.732 or x = -2.73

Therefore the roots are 0.732 and -2.73.

Hope that helps!

If you use the foil method, then it should be your original equation.

- Academic Writing
- Accounting
- Anthropology
- Article
- Blog
- Business
- Career
- Case Study
- Critical Thinking
- Culture
- Dissertation
- Education
- Education Questions
- Essay Tips
- Essay Writing
- Finance
- Free Essay Samples
- Free Essay Templates
- Free Essay Topics
- Health
- History
- Human Resources
- Law
- Literature
- Management
- Marketing
- Nursing
- other
- Politics
- Problem Solving
- Psychology
- Report
- Research Paper
- Review Writing
- Social Issues
- Speech Writing
- Term Paper
- Thesis Writing
- Writing Styles